2021
DOI: 10.1038/s41598-021-90308-1
|View full text |Cite
|
Sign up to set email alerts
|

Skyrmion crystals in centrosymmetric itinerant magnets without horizontal mirror plane

Abstract: We theoretically investigate a new stabilization mechanism of a skyrmion crystal (SkX) in centrosymmetric itinerant magnets with magnetic anisotropy. By considering a trigonal crystal system without the horizontal mirror plane, we derive an effective spin model with an anisotropic Ruderman–Kittel–Kasuya–Yosida (RKKY) interaction for a multi-band periodic Anderson model. We find that the anisotropic RKKY interaction gives rise to two distinct SkXs with different skyrmion numbers of one and two depending on a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 110 publications
5
43
0
Order By: Relevance
“…It can be applied to a generic form of the Hamiltonian, which includes not only two-spin but also multiple-spin interactions with any anisotropy. In recent years, several variations of such effective spin models have been studied for understanding of multiple-Q magnetic orderings in many materials, e.g., the skyrmion lattices in Gd 2 PdSi 3 [85], GdRu 2 Si 2 [73,74,86], Gd 3 Ru 4 Al 12 [78], and EuPtSi [76], and the hedgehog lattices in MnSi 1−x Ge x [62][63][64]. Our framework would be useful to clarify the complete phase diagrams and the nature of the transitions between different multiple-Q phases in a high resolution.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…It can be applied to a generic form of the Hamiltonian, which includes not only two-spin but also multiple-spin interactions with any anisotropy. In recent years, several variations of such effective spin models have been studied for understanding of multiple-Q magnetic orderings in many materials, e.g., the skyrmion lattices in Gd 2 PdSi 3 [85], GdRu 2 Si 2 [73,74,86], Gd 3 Ru 4 Al 12 [78], and EuPtSi [76], and the hedgehog lattices in MnSi 1−x Ge x [62][63][64]. Our framework would be useful to clarify the complete phase diagrams and the nature of the transitions between different multiple-Q phases in a high resolution.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…In addition, the multiple-Q spin configuration in Eq. ( 1) can describe other periodic topological spin textures, such as a hedgehog lattice [40][41][42][43][44][45][46], meron-antimeron crystal [47][48][49][50][51][52][53][54][55], and vortex crystal [56][57][58][59][60][61][62].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the early studies based on the antisymmetric DM interaction, recent discoveries of SkX and hedgehog lattices in centrosymmetric magnets [14,15,18,28] open up the possibility that various multiple-Q states can emerge by symmetric anisotropic exchange interactions. In fact, some model calculations have clarified that such a symmetric anisotropic exchange interaction stabilizes the multiple-Q states including the SkXs in centrosymmetric crystals with the space group P 4/mmm [51,52,88,89] P 6/mmm [54,[90][91][92], and P 3m1 [61,85,93]. However, there have been few studies focusing on the symmetric anisotropic exchange interactions in spite of various types of them depending on the crystal symmetry classified by the space group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the long-range nature of the interaction like the Ruderman-Kittel-Kasuya-Yosida (RKKY) interaction [81,82,83] in itinerant magnets is different from the short-range one in frustrated insulating magnets, an effective multi-spin interaction arising from the Fermi surface instability gives rise to the groundstate SkX even without the DM interaction [78]. Similar to the frustrated magnets, it was shown that the effect of single-ion anisotropy [84,85,86,87], two-ion anisotropy [88,89,90,91,92,93], circularly polarized microwave field [94], and thermal fluctuations [95,96] enhance the stability of the SkX. It was also shown that the introduction of the DM or antisymmetric spin-orbit interaction in itinerant magnets leads to the SkX formation [43,97,98,99,100].…”
Section: Introductionmentioning
confidence: 99%